Google Apps Script : a project-based exercise using spreadsheets and web apps - Svekis, Laurence (Packt Publishing, 2019)
"Learn the power of Google Script and see how you can connect Google Spreadsheet as a data source for a post board. Do you want to connect Google Apps together and make some really amazing things happen? Course will provide you the foundation to work with Google Script to build a Web App that can be embedded in Google Sites. Within the course we show you how to use Google Spreadsheet as a source for retrieving and storing data. Power up what you do online, bringing together built in functionality in your Google Suite. JavaScript developers extend your knowledge and learn how you can use your skills to develop apps script bringing together all the power of Google's Apps."--Resource description page